An ethnobotanical survey of medicinal plants used by diabetes patients attending the Teaching Hospital, Jaffna, Sri Lanka - Niluka, N.; Sathya, S.; Sivasinthujah, S. (Ceylon Journal of Science, 2024)
The scope of this study is to describe the ethnobotany of medicinal plants used in the management of diabetes mellitus (DM) among diabetic patients attending the Teaching Hospital, Jaffna. A cross-sectional descriptive study was conducted among 388 patients attending the medical clinic of Teaching Hospital, Jaffna, using systematic sampling technique. Data were collected using a validated structured interviewer-administered questionnaire and were analysed to generate the summary of the percentages using descriptive statistics. Family Important Value (FIV) and Related Frequency Citation (RFC) were calculated to quantitatively determine the common consent between the informants on the use of endemic medicinal plants in the division. A total of 59 species belonging to 33 families were reported by 329 diabetic patients with the response rate of 100%. Among them Moringa oleifera Lamk. (142) was stated as the species with the highest RFC value, followed by Gymnema sylvestre (105), Momordica charantia Linn. (104). Moringaceae was the most dominant family with FIV 43.16. The value of RFC of the plants mentioned in this survey varied from 0.003 to 0.432. Moringa oleifera Lamk. showed the highest RFC value (0.432). In this study, 29 plant species used for DM management were reported for the first time in Sri Lanka. Further, antidiabetic property of Achyranthus polygonoides, Argyreia pomacea Wall. ex Choisy and Cassia tomentosa are yet to be investigated. These findings facilitate the documentation and the conservation of medicinal plants used for DM by the patients in Teaching Hospital, Jaffna, Sri Lanka. Moreover this study open doors for phytochemical screening and identification of new antidiabetic active compounds. Keywords: Diabetes mellitus; Ethnobotany; Medicinal plants; Patients; Jaffna; Diabetic patients